8(3a+7c)-6(2a+6c)=

Simple and best practice solution for 8(3a+7c)-6(2a+6c)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(3a+7c)-6(2a+6c)= equation:


Simplifying
8(3a + 7c) + -6(2a + 6c) = 0
(3a * 8 + 7c * 8) + -6(2a + 6c) = 0
(24a + 56c) + -6(2a + 6c) = 0
24a + 56c + (2a * -6 + 6c * -6) = 0
24a + 56c + (-12a + -36c) = 0

Reorder the terms:
24a + -12a + 56c + -36c = 0

Combine like terms: 24a + -12a = 12a
12a + 56c + -36c = 0

Combine like terms: 56c + -36c = 20c
12a + 20c = 0

Solving
12a + 20c = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-20c' to each side of the equation.
12a + 20c + -20c = 0 + -20c

Combine like terms: 20c + -20c = 0
12a + 0 = 0 + -20c
12a = 0 + -20c
Remove the zero:
12a = -20c

Divide each side by '12'.
a = -1.666666667c

Simplifying
a = -1.666666667c

See similar equations:

| (2a^2b+7ab^2)+(3ab^2-2a^2b)= | | 8+2s-7=7s+3-4s | | -(3y+1)-(-2y-4)=-1 | | 3(x-2)(x+1)=0 | | -2y+6=20 | | 4z-7=5(5z-3) | | (5b-1)(6b-3)= | | 2x+20=304 | | -6x-(9y+(5x-(-2y-b))-(2b+a))= | | 2t^2-20t=0 | | 2(3v-1)+7v+7=5(v-6)+3v | | 304=s+20 | | 304=s+20w | | (4+w)(5w-8)=0 | | 30+9y=16y | | 5(w+2)-6(w+4)=0 | | (-6x-z)-(3y+(7x-(3z+8y+x)))= | | (5w+6)(5w-6)= | | -X+2x^2=0 | | -(8y+2)-(-7y-5)=-1 | | B=b+2a+3c | | 8(3x-8)=2(12x+7) | | (18y^2-12xy)-(6y^2+xy-a)= | | 3+3s-2=8s+5-3s | | 4(3w+1)+4v=4(v-6)-2v | | 6t+8t=84 | | 9ln(4x)=54 | | 6ay^3+5ay^2-4ay= | | (2.25c-9.28b+3.82a)-(-3.92a-1.72b-8.33c)= | | 2p=5p+9 | | 90=2x*3x+1+5*5 | | -8(3b+2)+(25b-9)=0 |

Equations solver categories